The teaching of mathematical problem-solving in Swedish classrooms: a case study of one grade five teacher’s practice - Pansell, Anna; Andrews, Paul (NOMAD Nordic Studies in Mathematics Education, 2017)
In this paper we examine the teaching of mathematical problem-solving to grade five students of one well-regarded and experienced Swedish teacher, whom we call Mary. Working within a decentralised curriculum in which problem-solving is centrally placed, Mary is offered little systemic support in her professional decision making with respect to problem-solving instruction. Drawing on Lester’s and Schroeder’s descriptions of teaching for, about and through problem-solving, we draw on multiple sources of data, derived from interviews and videotaped lessons, to examine how Mary’s problem-solving-related teaching is constituted in relation to the weakly-framed curriculum and the unregulated textbooks that on which she draws. The analyses indicate that Mary’s emphases are on teaching for and about problem-solving rather than through, although the ambiguities that can be identified throughout her practice with respect to goals, curricular aims and the means of their achievement can also be identified in the curricular documents from which she draws.